Optimizing The Cognitive Trend Through The Alternating Change Of Employees' Tasks - Jabbar Majeed Al-dedah, Hashim (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this paper is to analyze the best methods that can be used to optimize cognitive trends by adopting the Public Directorate of Citizens Services alternating change of the worker's tasks. A conceptual framework model is designed based on the research questions and their hypotheses. This study targets 7 different departments. Out of 199 workers who were invited to participate, 98 workers responded to this study. The descriptive method was used to analyze the collected data. It has a variety of quantitative and qualitative methods to prove the validity of hypotheses and research purposes. The significant finding of this study was optimizing cognitive trends for the majority of staff who have responded to this questionnaire after changing their tasks. They have confirmed several of the benefits obtained with this cognitive trend, such as developing their employees task skills, increasing their knowledge, promotion, and improving the work style. In the context of global organizations, it is important to identify the most important components of cognitive trends towards critical or common issues to evaluate the current organization's performance and determine the efficiency of its activities and efforts.